Euthanasia Dalam Epos Wiracarita Ramayana Sebagai Jalan Pembebasan - Arta, I Gede Arya Juni; Handoko, Handoko; Pernando, Pernando (Fakultas Dharma Duta, 2021)
Euthanasia means a gentle, comfortable and good death process, especially for patients who are full of suffering and do not have the potential to recover. Euthanasia has become a world discourse, where various groups in various scientific fields have discussed this problem, but until now it has not been completely and objectively resolved. The issue of euthanasia has always been an actual problem, and immediately caused various kinds of debate. This research is a library research, and is focused on qualitative research. Based on the results of research that has been carried out, it can be seen that euthanasia has occurred long before modern medical science developed, and is explicitly explained in Hindu literature, namely in the Rāmāyaṇa epic chapter or part of the 4th book called Kiskinda Kanda. Where the act of euthanasia carried out on Vālī, the king of the Kiskinda kingdom, was passive euthanasia or usually more accepted as